Linked-trip effects of 'town-centre-first' era foodstore development: An assessment using difference-in-differences. Issue 1 (January 2017) - Lambiri, Dionysia; Faggian, Alessandra; Wrigley, Neil
High levels of out-of-centre foodstore developments in the 1980s and early 1990s significantly altered the commercial landscape of the UK, and were widely seen as threatening the vitality and viability of small and medium-sized centres. The progressive tightening of retail planning regulation in the decade that followed, and retailer adaptation to that tightening, resulted in the development of more flexible foodstore formats suited to in-centre or edge-of-centre sites, which worked 'with the grain' of the 'town centre first' approach to retail planning policy. Since then academic research has started to suggest a more positive role for such developments than hitherto, and to indicate that they can play an important role in anchoring small centres. The key mechanism underlining this potential positive role is that of linked trips, whereby the spatial externality generated by a foodstore development is transmitted to the existing retail structure of the centre in which development has occurred. Even though UK planning policy has consistently viewed the role of linked shopping trips as critical to town centre vitality, available evidence on this key issue remains remarkably scarce and dated in terms of the planning regulation context from which it was generated. This paper aims to fill that gap. We make use of a large and unique database on consumer shopping behaviour collected over the period August 2007–November 2009 in selected UK centres, and employ the difference-in-differences method to obtain insight into the hypothesised uplift in linked trip propensity which can be attributed to a foodstore development. Our results indicate that the development of new-generation foodstores in in-centre and edge-of-centre locations does indeed increase the propensity of shoppers to link their trips between foodstores and town centre shops/services. Controlling for shoppers' individual characteristics, that increase is shown to be over seven percentage points. The exact numerical value is likely to be sample specific, and its typical range will only be established by replication. However, the importance of the finding is that using sophisticated but appropriate statistical methodology and a large sample of data from a transparently designed and rigorously conducted study, the development of 'new-generation' town-centre first foodstores is clearly associated with increased linked trip propensities. To our knowledge, this is the first time unambiguous evidence of the existence of this hypothesised 'town centre first era' linked-trip effect has been demonstrated.